Perbandingan Penerapan Notifikasi Terkait Tindakan Akuisisi Berdasarkan Hukum Persaingan Usaha di Indonesia dan Singapura: - Alvalaneda; Dian Purnamasari (Reformasi Hukum Trisakti, 2023)
Indonesia’s competition law comprehends acquisition procedures in article 29 of Law No.5/1999 jo. Article 5 of Government Regulation No.57/2010 and KPPU guidelines about the acquisition, meanwhile Singapore has the same regulations through Article 54 of the SCA 2004 along with CCCS guidelines on M&A. Both countries apply different acquisition regulations as well as the application of notification concept, so that it’s become a problem to analyze KPPU Juridical Verdict No.30/KPPU-M/2020 and CCCS NID Case Number: 500/01/18 to know the similarities and differences. Therefore, this research used juridical normative method by examining secondary data and analyzing it qualitatively. The result of the research shows that there are differences in acquisition regulation such as differences in notification regime, threshold for notification, valuation method, and the use of public consultation in Singapore while the similarities include consideration of financial penalties and costs assessment. It can be concluded that both countries apply different notification regime, and Singapore not only use written law but also unwritten law, meanwhile Indonesia only use written law.